TINGKAT PENGETAHUAN KESEHATAN GIGI DAN MULUT PADA GURU DAN MURID SDN 16 (UKGS) DAN SDN 46 (TANPA UKGS) DI KOTA BANDA ACEH - Cut Fera Novita; Her wanda; Muh ajir (FKG Unsyiah, 2017)
Knowledge in the field of oral health provides an understanding of how to do maintenance and prevention of dental and oral diseases. Teachers can act as a source of information for students so that they are expected to have sufficient knowledge about dental and oral health applied in the UKGS program. The purpose of this study was to find out how the level of oral and dental knowledge in teachers and students in primary schools with UKGS and without UKGS. The type of research is descriptive. The sampling technique used total sampling method with total research subjects that fulfilled inclusion criteria of 39 teachers and 80 students, consisting of 24 teachers and 64 students in SDN 16 (UKGS) and 15 teachers and 16 students in SDN 46 (without UKGS). Measurement of dental and oral health knowledge was done by using questionnaire. The results showed that the level of knowledge of dental and mouth health of teachers and students at SDN 16 (UKGS) and SDN 46 (without UKGS) had good category with 87.5% percentage for teachers and 82.8% for pupils in SDN 16 (UKGS ) and 80% for teachers and 68.8% for students in SDN 46 (without UKGS). Keywords: UKGS, knowledge, teachers, students